Contradições entre o campo e a cidade no Triângulo Mineiro: uma reflexão sobre o fechamento das escolas no campo - Nogueira, Ariane Martins (2019)
The integration of the agro-exporting economy with an urban-industrial model has led to the emergence of innumerable social dilemmas, such as: land concentration, rural flight, urban sprawl, among other issues that have changed the way in which the Brazilian society produces, consumes and lives. In this scenario, we seek to understand the causes and consequences of the closure of rural schools, mainly by interpreting this process as a factor to legitimize rural emptying, to make land available for the agrobusiness spread and also as a strategy used to dismantle communities and to uproot the identity of future generations with the countryside. Between 2010 and 2018, 21,822 public schools were closed in rural areas. In the state of Minas Gerais, a total of 1,751 schools were closed – of which 1,644 are municipal schools. This is the problem we start from and the centrality of this study is the Triângulo Mineiro region, with statistical data indicating that it is increasingly being transformed into an “agricultural” region, destined to industries, empty of people and full of monocultures of sugarcane and grains. The diverse, multifaceted rural is increasingly more “residual”. The empirical research was carried out in twelve municipalities from Triângulo Mineiro: Água Comprida, Campo Florido, Carneirinho, Comendador Gomes, Conquista, Gurinhatã, Ipiaçu, Limeira do Oeste, Pirajuba, São Francisco de Sales, União de Minas e Veríssimo. Interviews were conducted in the Municipal Education Offices, since it is specifically the municipal sphere that holds the highest rates of closed schools. It could be observed arguments that closing the schools is necessary to contain expenditures or that it is a consequence of the lack of students. In contrast, exorbitant amounts of money were destined for student transportation. It was also found that the decision to close schools happens unilaterally at the municipal administrative level, with the community being rarely consulted during the process. Among the municipalities surveyed, there are still active municipal rural schools only in Campo Florido, Gurinhatã and Limeira do Oeste. In the other municipalities, all schools were deactivated and about 1,800 students are transported to urban schools on a daily basis. The journey usually takes one a half hours each way. That scenario features a notorious negligence with rural populations, as they are accounted for only in terms of numbers and values, having their right to land, work and education constantly neglected by the State.